PENGARUH INTERNAL LOCUS OF CONTROL DAN RISK TAKING BEHAVIOR TERHADAP INTENSI KEWIRAUSAHAAN MAHASISWA UNIVERSITAS MUHAMMADIYAH PROF. DR. HAMKA - Yasir Wiratmanto; Puty Archianti Widiasih (Prosiding Seminar Nasional Berseri, 2020)
The Research aims to determine the influence of internal locus of control and risk taking behavior towards the entrepreneurial intention OF University students Prof. DR. Hamka. Internal locus of control and risk taking behavior are predictors in the formation of entrepreneurial intentions. This research is a quantitative study. The participants in this study were active students of Muhammadiyah University PROF. DR. Hamka force of 2015 and 2016 amounting to 235 people consisting of men and women. The scale Model used is the Likert scale. The Study used multiple regression analyses using the Help OF IBM SPSS Statistic V. 22. Based on the results of R Square 0.097 which means the determination between internal locus of control and risk taking behavior against entrepreneurial intention of 9.7% and probability value value of 0.000 which means significant as well as unstanderdized value coefficient B internal locus of control of 0256 and risk taking behavior of 0183 which means positive. From these results can be concluded a significant positive influence between internal locus of control and risk taking behavior against the intention of entrepreneurship UNIVERSITY students PROF. DR. Hamka.